Analysis of Village Government Programs in Tourism Development - Anggita Putri, Aulia; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2022)
This study aims to analyze and describe the tourism development program in Watesnegoro Village. This research is based on the fact that the promotion carried out by the Village Government and tourism management has not gone as expected, so that this tour is not yet known by the general public. The research method used in this research is using descriptive qualitative, data collection is done through interviews, observation, and documentation, as well as data analysis techniques used in this study refers to the theory of Miles and Huberman. The results showed that the program carried out by the Watesnegoro Village Government in developing gadung source tourism was by promoting through mass media where the Watesnegoro Village Government collaborated with Radar Mojokerto to promote this tourism to be known by the general public, the Watesnegoro Village Government also plans to carry out additional promotions through web and accounts on social media. Instagram and Facebook are social media applications chosen by the Village Government and tourism managers in promoting the tourism. In addition, the Watesnegoro Village Government will also conduct socialization to the general public, and will coordinate with the Mojokerto Regency Youth, Sports, Culture and Tourism Office.